Land, power and conflict in Afghanistan: seeking to understand complexity - Adam Pain (Revue des Mondes Musulmans et de la Méditerranée)
This paper explores the diverse links between land and power under conditions of conflict in Afghanistan, taking into account the complexities of Afghan society. These complexities are structured around interconnecting informal institutions and personalised relationships, culturally specific, diverse and shifting patterns of social relations, and spatially specific patterns of land ownership inequalities. The paper draws on a decade of empirical fieldwork in Afghanistan and recent work on livelihood trajectories and the opium economy. An understanding of the evolution of land ownership and access issues needs to be associated with an appreciation of diverse and potentially contradictory long-term drivers of change in the rural economy. The first of these long-term drivers of change relates to the effects of conflict, not only on land but also of water access under conditions of an increasingly scarce water supply. The second driver relates both to the roles played by village elites and to the structural contrasts between villages located in the mountains and in the plains, with the latter displaying major inequalities in land ownership. The third driver relates to the declining economic role of land in rural livelihoods, given long-term agrarian change and falling farm sizes. An understanding of history is fundamental to explaining these phenomena. How such conflicts play out, and which social groups or individuals they involve, also depend to a large degree on spatial positioning.